Prevalence and Risk Factors of COPD in Nepal: A Systematic Review and Meta-Analysis - Budhathoki, Pravash; Shrestha, Dhan Bahadur; Sedhai, Yub Raj; Baniya, Ramkaji; Bhatt, Ayush; Chaudhary, Kabita; Acharya, Astutee; Rajkarnikar, Ruja; Basnet, Madan; Atreya, Alok (Journal of Nepal Health Research Council, 2022)
Background: Chronic Obstructive Pulmonary Disease is a common, preventable, and treatable disease. Here, we conducted a systematic review of Chronic Obstructive Pulmonary Disease and its risk factors in Nepal for the last two decades. Methods: We systematically searched databases to find all relevant Chronic Obstructive Pulmonary Disease research papers from 2000 to 2020. Two reviewers screened the literature using Covidence based on the study protocol. Data extraction was done using Microsoft Excel from selected studies. Final data analysis was done using CMA v.3. Our review protocol is available in PROSPERO (CRD42020215486) on 20 November 2020. Results: The database search revealed 1416 studies of which 13 were included in quantitative analysis. The prevalence of Chronic Obstructive Pulmonary Disease in the adult population was 22·7% (CI, 12·5-37·7) of whom 54·9% were female (CI, 51·9-57·9). Nearly three-fourth of the participants (73·1%) of Chronic Obstructive Pulmonary Disease patients had informal education (CI, 58·6-84·0). The commonest primary occupation was agriculture and farming in 39·4% (CI, 31·3-48·2), followed by homemaker (36·8%). It was observed that 28·5% of the Chronic Obstructive Pulmonary Disease patients were former smokers, 25·8% non-smokers, and 59·4% were current smokers. More than two-third (76·2%) of Chronic Obstructive Pulmonary Disease patients relied upon traditional firewood cooking, whereas only 14.6% was adopted fireless cooking. Conclusions: The pooled prevalence of Chronic Obstructive Pulmonary Disease in Nepal was significantly high with more cases in females compared to males. Smoking and traditional firewood cooking were major risk factors among Chronic Obstructive Pulmonary Disease cases in Nepal. Keywords: Chronic obstructive pulmonary disease; cooking; tobacco smoking.